Rapid efficient synthesis and characterization of silver, gold, and bimetallic nanoparticles from the medicinal plant plumbago zeylanica and their application in biofilm control - Salunke, Gayatri R.; Ghosh, Sougata; Kumar, R. J. Santosh; Khade, Samiksha; Vashisth, Priya; Kale, Trupti S.; Chopade, Snehal; Pruthi, Vikas; Kundu, Gopal; Bellare, Jayesh R.; Chopade, Balu Ananda (International Journal of Nanomedicine, 2014)
Background: Nanoparticles (NPs) have gained significance in medical fields due to their high surface-area-to-volume ratio. In this study, we synthesized NPs from a medicinally important plant - Plumbago zeylanica. Materials and methods: Aqueous root extract of P. zeylanica (PZRE) was analyzed for the presence of flavonoids, sugars, and organic acids using high-performance thin-layer chromatography (HPTLC), gas chromatography-time of flight-mass spectrometry (GC-TOF-MS), and biochemical methods. The silver NPs (AgNPs), gold NPs (AuNPs), and bimetallic NPs (AgAuNPs) were synthesized from root extract and characterized using ultraviolet-visible spectra, X-ray diffraction (XRD), energy-dispersive spectrometry (EDS), transmission electron microscopy (TEM), and dynamic light scattering (DLS). The effects of these NPs on Acinetobacter baumannii, Staphylococcus aureus, and Escherichia coli biofilms were studied using quantitative biofilm inhibition and disruption assays, as well as using fluorescence, scanning electron microscopy, and atomic force microscopy. Results: PZRE showed the presence of phenolics, such as plumbagin, and flavonoids, in addition to citric acid, sucrose, glucose, fructose, and starch, using HPTLC, GC-TOF-MS, and quantitative analysis. Bioreduction of silver nitrate (AgNO3) and chloroauric acid (HAuCl4) were confirmed at absorbances of 440 nm (AgNPs), 570 nm (AuNPs), and 540 nm (AgAuNPs), respectively. The maximum rate of synthesis at 50 degrees C was achieved with 5 mM AgNO3 within 4.5 hours for AgNPs; and with 0.7 mM HAuCl4 within 5 hours for AuNPs. The synthesis of AgAuNPs, which completed within 90 minutes with 0.7 mM AgNO3 and HAuCl4, was found to be the fastest. Fourier-transform infrared spectroscopy confirmed bioreduction, while EDS and XRD patterns confirmed purity and the crystalline nature of the NPs, respectively. TEM micrographs and DLS showed about 60 nm monodispersed Ag nanospheres, 20-30 nm Au nanospheres adhering to form Au nanotriangles, and about 90 nm hexagonal blunt-ended AgAuNPs. These NPs also showed antimicrobial and antibiofilm activity against E. coli, A. baumannii, S. aureus, and a mixed culture of A. baumannii and S. aureus. AgNPs inhibited biofilm in the range of 96%-99% and AgAuNPs from 93% to 98% in single-culture biofilms. AuNPs also showed biofilm inhibition, with the highest of 98% in S. aureus. AgNPs also showed good biofilm disruption, with the highest of 88% in A. baumannii. Conclusion: This is the first report on rapid and efficient synthesis of AgNPs, AuNPs and AgAuNPs from P. zeylanica and their effect on quantitative inhibition and disruption of bacterial biofilms.
Keywords: AgAuNPs; AgNPs; AuNPs; biofilm inhibition and disruption; GC-TOF-MS; P. zeylanica

Synthesis, DNA interaction and anticancer activity of 2-anthryl substituted benzimidazole derivatives - Sontakke, Vyankat A.; Kate, Anup N.; Ghosh, Sougata; More, Piyush; Gonnade, Rajesh G.; Kumbhar, Navanath M.; Kumbhar, Anupa A.; Chopade, Balu Ananda; Shinde, Vaishali S. (New Journal of Chemistry, 2015)
2-Anthryl benzimidazole derivatives (5-7) with hydrogen, carboxyl and benzoyl substituents at the 5th position have been synthesized using a silica supported periodic acid catalyst. The DNA cleavage activity of 5-7 was studied in the presence of light using pBR322 plasmid DNA and was shown to vary with substitution at the 5th position of benzimidazole derivatives. DNA binding studies using ethidium bromide displacement assay demonstrated the non-intercalative binding mode of 5-7. The anticancer activity of these target molecules was tested against MCF-7 and HL-60 cell lines, and they exhibited remarkable activity in the micromolar range. Cellular uptake and morphological changes were confirmed by fluorescence and confocal microscopy. A molecular docking study was carried out to explore the DNA binding mechanism of 5-7.

Antimicrobial synergy of silver-platinum nanohybrids with antibiotics - Ranpariya, Bansi; Salunke, Gayatri; Karmakar, Srikanta; Babiya, Kaushik; Sutar, Santosh; Kadoo, Narendra; Kumbhakar, Pathik; Ghosh, Sougata (Frontiers in Microbiology, 2021)
Various bacterial pathogens are responsible for nosocomial infections resulting in critical pathophysiological conditions, mortality, and morbidity. Most of the bacterial infections are associated with biofilm formation, which is resistant to the available antimicrobial drugs. As a result, novel bactericidal agents need to be fabricated, which can effectively combat the biofilm-associated bacterial infections. Herein, for the first time we report the antimicrobial and antibiofilm properties of silver-platinum nanohybrids (AgPtNHs), silver nanoparticles (AgNPs), and platinum nanoparticles (PtNPs) against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The AgPtNHs were synthesized by a green route using Dioscorea bulbifera tuber extract at 100 degrees C for 5 h. The AgPtNHs ranged in size from 20 to 80 nm, with an average of similar to 59 nm. AgNPs, PtNPs, and AgPtNHs showed a zeta potential of -14.46, -1.09, and -11.39 mV, respectively. High antimicrobial activity was observed against P. aeruginosa and S. aureus and AgPtNHs exhibited potent antimicrobial synergy in combination with antibiotics such as streptomycin, rifampicin, chloramphenicol, novobiocin, and ampicillin up to variable degrees. Interestingly, AgPtNHs could inhibit bacterial biofilm formation significantly. Hence, co-administration of AgPtNHs and antibiotics may serve as a powerful strategy to treat bacterial infections.
Keywords: antibiofilm; antimicrobial synergy; biogenic synthesis; Characterization; silver-platinum nanohybrids

Catechin-capped silver-doped titanium dioxide nanoparticle enhanced photocatalytic toxic dye degradation - Ghosh, Sougata; Imboon, Tanawat; Layek, Rashbihari; Salunke, Gayatri; Parihar, Vijay Singh; Khumphon, Jeerawan; Webster, Thomas J.; Sutar, Santosh; Kityakarn, Sutasinne; Issro, Chaisak; Khamboonrueang, Dusadee; Thongmee, Sirikanjana (Frontiers in Chemistry, 2025)
Doping-associated surface modification is a powerful strategy to enhance the photocatalytic potential of n-type semiconductor nanomaterials. Silver (Ag) is one of the most effective dopants that can result in the retardation of the electron hole recombination-generating Schottky barrier at the TiO2 interface with a simultaneous extension of absorption to the visible region. This work presents a study on the effect of catechin, a bioactive principle polyphenol compound found in various plants, on the synthesis, Ag-doping and stabilization of TiO2 nanoparticles (TiO2NPs). The nanoparticles were irregular in shape with sizes ranging from 19 to 30 nm. Ag-TiO2NPs were fabricated using TiO2 as a precursor and 1%, 3%, and 5% AgNO3 as a doping agent. The average particle size of 1%Ag-TiO2NPs, 3%Ag-TiO2NPs, and 5%Ag-TiO2NPs was 27.3 +/- 7.5 nm, 29.8 +/- 9.6 nm, and 25.0 +/- 9.0 nm, respectively. High-resolution transmission electron microscopy (HRTEM) showed lattice fringes with an interplanar spacing of 0.23 nm corresponding to the Ag (111) plane in addition to the presence of the anatase phase of TiO2. Fourier transform infrared (FTIR) spectra exhibited a broad peak around 400-800 cm-1 that was attributed to Ti-O-Ti stretching vibrations which was slightly shifted in Ag-TiO2NPs due to changes in the local bonding environment around Ti atoms caused by interactions with Ag. Catechin loading in the TiO2NPs and Ag-TiO2NPs was between 1.55 and 3.3 wt. %. TiO2NPs, 1%Ag-TiO2NPs, 3%Ag-TiO2NPs, and 5%Ag-TiO2NPs exhibited superior photocatalytic degradation of methylene blue dye up to 78%, 87%, 91%, and 92%, respectively, and RhB dye up to 92%, 94%, 97% and 99%, respectively, with a pseudo-first-order reaction kinetics. Furthermore, its recyclability was also demonstrated for three cycles. The simplicity of fabrication and superior photocatalytic performance of TiO2 demonstrated here make this green route advantageous for environmental applications to treat dye contaminated effluent as well as for numerous other applications.
Keywords: catechin; green synthesis; methylene blue dye; Photocatalysis; Rhodamine B; silver doping; titanium dioxide nanoparticles